Perspektywy rozwoju energetyki odnawialnej w województwie śląskim - Lorek, Agnieszka (Prospects of Renewable Power Industry Growth in Silesian Voivodeship, 2009)
The renewable sources of energy rational use is one of sustainable development priorities which bring measurable economic, social and ecological effects. This is also one of the Silesian voivodeship priorities. Taking into consideration present, possible to use technologies, the voivodeship offers average on the scale of Poland possibilities of production of energy from renewable energy sources. The exception is biomass energy which potential is estimated as large and energy from mine waters which can be the source of thermal energy for large agglomerations. Profitable conditions to use solar energy to the production of warm usable water also appear in the whole voivodeship.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 71-81